2017
DOI: 10.3892/ol.2017.6880
|View full text |Cite
|
Sign up to set email alerts
|

The role of LASS2 in regulating bladder cancer cell tumorigenicity in a nude mouse model

Abstract: Previous in vitro studies have demonstrated that LAG1 longevity assurance homolog 2 (LASS2) is a novel tumor suppressor gene that is significantly associated with the proliferation and invasion ability of tumor cells. However, the role LASS2 serves in regulating bladder cancer cell tumorigenicity and tumor growth in vivo has not yet been elucidated in animal or clinical studies. In the present study, LASS2 knockdown in human bladder cancer EJ-M3 cells significantly promoted the growth of xenografts in nude mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This correlation has also been tested experimentally, using nude mice to study the evolution of xenografts with a highly invasive human BC cell line. Indeed, when CERS2 was silenced in the xenografts, the resulting tumors significantly increased in volume [60]. Also supporting the tumor suppressor activity of CERS2, an epidemiology study based on SNPs showed that a particular substitution, which favors RNA instability and reduces transcript abundance, acts as an independent risk factor of BC susceptibility and clinical prognosis in the Chinese population [24].…”
Section: Cers2 Expression In Bcmentioning
confidence: 83%
“…This correlation has also been tested experimentally, using nude mice to study the evolution of xenografts with a highly invasive human BC cell line. Indeed, when CERS2 was silenced in the xenografts, the resulting tumors significantly increased in volume [60]. Also supporting the tumor suppressor activity of CERS2, an epidemiology study based on SNPs showed that a particular substitution, which favors RNA instability and reduces transcript abundance, acts as an independent risk factor of BC susceptibility and clinical prognosis in the Chinese population [24].…”
Section: Cers2 Expression In Bcmentioning
confidence: 83%
“…C16:0 ceramides have been shown to play a pivotal role in cell migration during epithelial to mesenchymal transition in different cancer cell lines 59 . In contrast, overexpression of CERS2, that synthesizes very-long-chain ceramides, has been demonstrated to inhibit cancer cell proliferation and migration in prostate, breast, and bladder cancers 60 , 61 . Luminal B-specific BT-474 cells overexpressing PC transcript of CERS2 showed a significant decrease in cell proliferation and migration due to an increase in levels of very-long-chain ceramides.…”
Section: Discussionmentioning
confidence: 99%
“…20190325) and were performed in compliance with all regulatory institutional guidelines for animal welfare (the National Institutes of Health Publications no. 80-23) ( 23 ). A total of 12 male BALB/c-nu mice (4-week-old, 20±5 g; Hunan SJA Laboratory Animals Center of the Chinese Academy of Sciences) were used in this study.…”
Section: Methodsmentioning
confidence: 99%